CFD Based Optimization and Design of a Feeding Tube Enhanced Cross Flow Heat Exchanger for Automotive Heat Transfer Systems - Navas, Mohammed Irfan (2025)
A Master of Science thesis in Engineering Systems Management by Mohammed Irfan Navas entitled, “CFD Based Optimization and Design of a Feeding Tube Enhanced Cross Flow Heat Exchanger for Automotive Heat Transfer Systems”, submitted in November 2025. Thesis advisor is Dr. Noha Mohamed Hassan and thesis co-advisor is Dr. Mohammad O. Hamdan. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).